Electrodeposition of lead dioxide induces the fabrication of perovskite FAPbI3 film and electron-transport-layer-free solar cells. (February 2022) - Li, Qiang; Lu, Congrong; Li, Chunhe; Ren, Kuankuan; Yao, Bo; Xu, Haitao; Liu, Shiyan; Tan, Yongsheng; Dou, Weidong; Fang, Zebo
Highlights: Pure perovskite α-FAPbI3 film was synthesized by the electrodeposition method. MABr addition can suppress the size and number of pinholes in the perovskite FAPbI3 film. The best efficiency of PbO2 induced ETL-free FAPbI3 solar cells is nearly 20 times higher than that of PbI2 based solar cells. Abstract: Formamidinum based lead halide (α-FAPbI3 ) perovskite solar cells have refreshed the highest power conversion efficiency several times in the best Research-Cell Efficiency Chart due to its suitable bandgap. However, the non-perovskite yellow phase δ-FAPbI3 is easily formed in the process of synthesizing the black phase α-FAPbI3 . To solve this problem, we provide a new method to grow pure perovskite α-FAPbI3 film through electrodeposited lead dioxide (PbO2 ). The as-prepared α-FAPbI3 shows an obvious absorption edge despite some pinholes formation during the reaction of PbO2 and FAI. By adding extra MABr during the synthesis of α-FAPbI3, the size and number of pinholes can be effectively suppressed. Thus, the optimal electron-transport-layer (ETL)-free perovskite FAPbI3 solar cells show a drastically elevated power conversion efficiency (PCE) of 10.73%, which is nearly 20 times higher than that of PbI2 based perovskite solar cells with the same device structure. These results demonstrate that the growth of PbO2 film by the electrodeposition method provides a new way for the preparation of high-efficiency perovskite solar cells. On this basis, combined with the introduction of the ETL (TiO2, SnO2, etc.) and the optimization of device fabrication processes, the PCE of the perovskite solar cells obtained by this method may be further improved in the future.